Interactions Between Dynamic Softening and Strengthening Mechanisms During Hot Forging of a High-Strength Steel - Khan, Makarim; Shahriari, Davood; Jahazi, Mohammad; Morin, Jean-Benoit (Frontiers in Mechanical Engineering, 2021)
Open-die forging is a critical step in the manufacture of large numbers of components used in the transportation and energy industries. Dynamic recrystallization, dynamic transformation, and dynamic precipitation take place during the hot deformation process and significantly affect microstructure conditioning, which ultimately influences the service properties of the component. In the present work, using a Gleeble 3800 thermomechanical simulator, the open-die forging of a large-size ingot made of a modified AISI 6140 medium carbon high-strength steel is investigated. Deformation temperatures ranging from 950°C to 1,250°C and strain rates ranging from 0.01 to 1 s−1, representative of the actual process, are considered in the analysis. The generated true stress–true strain curves are used as a basis for the development of a constitutive model predicting the occurrence of softening and strengthening phenomena as a function of thermomechanical conditions. The corresponding activation energy is determined to be about 374 kJ mol−1 and is compared against the values reported in the literature for other high-strength steels. Dynamic recrystallization kinetics is studied using the t50 model, and the influence of temperature and strain rate is quantified and discussed. The interaction between dynamic precipitation and dynamic recrystallization is discussed, and the deformation conditions under which such interactions occur are determined. The thermomechanical results are validated by microstructure examination, including laser confocal microscopy, field emission scanning electron microscopy, transmission electron microscopy, and energy-dispersive spectroscopy. The present study focuses on reproducing the deformation cycle applied during the open-die forging process of a vanadium-containing high-strength steel used in the industry with special attention to the interaction between dynamic recrystallization and precipitation processes.